2017
DOI: 10.25011/cim.v40i2.28195
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of ADAMTS13 in patients with severe sepsis and septic shock

Abstract: Prognostic value of ADAMTS13 in patients with severe sepsis and septic shock Abstract Purpose: ADAMTS13 level was evaluated as a predictor of mortality in patients with severe sepsis and septic shock, and compared with Acute Physiology and Chronic Health Evaluation II (APACHE II) scores.Methods: This prospective observational study was conducted in the Medical and Surgical Intensive Care Units of King Khalid University Hospital. Detailed clinical evaluations were performed on 84 patients (56.08±18.18 years of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 34 publications
1
18
1
Order By: Relevance
“…This is the first study, to our knowledge, to associate the variation of VWF/ADAMTS-13 system disorders in sepsis have been associated with disease severity and increased mortality. [18][19][20] Particularly, in critically ill patients with severe sepsis or septic shock, ADAMTS-13 levels were lower than in ICU patients without sepsis; in the same study, decreased ADAMTS-13 levels were associated with increased APACHE II score at admission and predicted an increased risk of death in ICU. 18 Also, in patients with severe sepsis and septic shock, ADAMTS-13 levels were comparable to APACHE II score for predicting mortality.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…This is the first study, to our knowledge, to associate the variation of VWF/ADAMTS-13 system disorders in sepsis have been associated with disease severity and increased mortality. [18][19][20] Particularly, in critically ill patients with severe sepsis or septic shock, ADAMTS-13 levels were lower than in ICU patients without sepsis; in the same study, decreased ADAMTS-13 levels were associated with increased APACHE II score at admission and predicted an increased risk of death in ICU. 18 Also, in patients with severe sepsis and septic shock, ADAMTS-13 levels were comparable to APACHE II score for predicting mortality.…”
Section: Discussionmentioning
confidence: 68%
“…VWF/ADAMTS‐13 system disorders in sepsis have been associated with disease severity and increased mortality . Particularly, in critically ill patients with severe sepsis or septic shock, ADAMTS‐13 levels were lower than in ICU patients without sepsis; in the same study, decreased ADAMTS‐13 levels were associated with increased APACHE II score at admission and predicted an increased risk of death in ICU …”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…One recent study demonstrated an approximately 50% lower survival rate in patients (mortality of 59%) with septic shock and ADAMTS‐13 levels of < 30% than in patients with higher levels of ADAMTS‐13 (mortality of 28%) . The predictive value of ADAMTS‐13 deficiency for mortality was as powerful as those of APACHE II or similar risk scores .…”
Section: Prognostic Significance Of Adamts‐13mentioning
confidence: 99%
“…Interestingly, patients with severe sepsis and DIC may have reduced ADAMTS-13 levels (presumably due to consumption as a result of the large amount of von Willebrand factor multimers released from perturbed endiothelial cells) causing some overlap between DIC and thrombotic microangiopathy. 39 Raised VWF levels and associated reduced ADAMTS 13 levels, are associated with worse outcomes in severe DIC. 40 For personal use only.…”
Section: Comments About Patientmentioning
confidence: 99%